If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 2 + -3c Solving 4 = 2 + -3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3c' to each side of the equation. 4 + 3c = 2 + -3c + 3c Combine like terms: -3c + 3c = 0 4 + 3c = 2 + 0 4 + 3c = 2 Add '-4' to each side of the equation. 4 + -4 + 3c = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 3c = 2 + -4 3c = 2 + -4 Combine like terms: 2 + -4 = -2 3c = -2 Divide each side by '3'. c = -0.6666666667 Simplifying c = -0.6666666667
| 11=15+4n | | -3m+4=11 | | -2+2x=-x+2+x | | 6a+5=a | | 3x^2+15x-14=0 | | 8y+3=7 | | X^2+12=7x | | log(x+6)=log(3)+log(x) | | 5x^3+5x^2-40x-60=0 | | (3-y)(y+4)=3y-5 | | -13=-11y+9 | | y^2-5y=3 | | -7n-4=-25 | | 29-(3y-1)=2(y-1)+3y | | -(x-1)=-4x-2 | | -5d+3=-12 | | 8-(x-2)=3x+4 | | 56=12+4n | | 3x^2=7x-2 | | x^2-14z+45=0 | | 3x+7=9x-5 | | x^2+26x+120=0 | | 6-4x=7x-9x+10-4 | | (-2n-1)=7 | | 2-x=11 | | (2x+5)-(5x+4)=6-2(x-3) | | 7-c=9 | | a-7-7=5 | | 5+4t=8 | | 13=9+4z | | -7-7=5 | | -2+3x=-(x+6) |